Early delivery or expectant management for late preterm preeclampsia: A meta‐analysis of randomized controlled trials. (13th April 2021) - Chatzakis, Christos; Liberis, Anastasios; Zavlanos, Apostolos; Petousis, Stamatis; Tsakmaki, Evangelia; Dinas, Konstantinos; Sotiriadis, Alexandros
Abstract: Introduction: Currently, there is no consensus regarding the timing of delivery in women with non‐severe preeclampsia at the late preterm period. The aim of the present meta‐analysis is to compare expectant management with immediate delivery in pregnant women with preeclampsia between 34+0 and 36+6 gestational weeks, in terms of maternal and neonatal outcomes. Material and methods: A search was conducted until October 1, 2020 and eligible studies were identified in MEDLINE, Scopus, Cochrane Central Register of Controlled Trials (Central), the US Registry of clinical trials (www.clinicaltrials.gov ), and sources of gray literature without limitations concerning the publication dates and languages. Randomized controlled trials, comparing planned delivery vs expectant management in women with preeclampsia at 34–37 weeks were included. The primary outcomes were neonatal intensive care unit (NICU) admission and progression to eclampsia. Secondary outcomes were HELLP (hemolysis, elevated liver enzymes, and low platelet count) syndrome, severe preeclampsia, composite adverse maternal outcome (defined by the presence of any of the potential preeclampsia‐related complications, ranging from severe hypertension to maternal death), neonatal respiratory disease, and respiratory distress syndrome. Relative risks (RRs) and mean differences with 95% CI were used for the estimation of the effect sizes; the quality of the evidence was assessed per GRADE guidelines. Results: The electronic search yielded 10 721 potential studies, of which six were fully reviewed and three (1773 participants) were included in the meta‐analysis. Immediate delivery increased the risk for NICU admission, (RR 1.23, 95% CI 1.05–1.45) and decreased the risk for the composite adverse maternal outcome (RR 0.86, 95% CI 0.78–0.93). There were no differences for eclampsia (RR 0.55, 95% CI 0.16–1.85), HELLP syndrome (RR 0.58, 95% CI 0.25–1.33), severe preeclampsia (RR 0.27, 95% CI 0.02–3.52), respiratory disease of neonate (RR 1.04, 95% CI 0.75–1.44), and respiratory distress syndrome (RR 2.3, 95% CI 0.73–7.25). Conclusions: Immediate delivery of women with non‐severe preeclampsia at the period of late prematurity decreases the risk of a composite adverse maternal outcome by 14%, at the cost of an increase in NICU admissions by 23%. The overall quality of the evidence for these outcomes is high, indicating a high degree of certainty for the results.